Mga hulwarang modyul sa pagtuturo ng Pilipino sa mataas na paaralang bokasyonal sa kaligirang pangalawang wika - Macairan, Fe Tobawon 1950-
This research aimed to develop a set of materials showing the Integrated Approach in teaching Filipino as a Second Language in the secondary level among vocational schools through the so-called modularized instruction. This study involved two phases of the materials design: the design and the development phases. Based on the findings, the controlled test proved that the materials were appropriate and effective for the students because among fifty students on each year level, most has improved their skills through this type of instruction.